Incorporation of Municipalities and Population Growth A Propensity Score Matching Approach - Björn Kauder (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
During the 1960s and 1970s, the German state governments reduced the number ofmunicipalities. Many independent municipalities in the outskirts of a city became a district of the respective city. Using propensity score matching, I examine how thereforms influenced population growth in these incorporated units. The results show that the population of small incorporated municipalities grew by about 47 percentage pointsfaster than the population of small municipalities that remained independent. The resultsdo not show that large incorporated municipalities grew faster than large municipalities that remained independent. Population growth was stronger in municipalities that wereincorporated later.
Keywords: H11; H77; R23; 330; Municipality reform; administrative structure; population growth; propensity score matching